Organizational health climate as a precondition for health-oriented leadership: expanding the link between leadership and employee well-being - Teetzen, Friederike; Klug, Katharina; Steinmetz, Holger; Gregersen, Sabine (Frontiers in Psychology, 2023)
The link between leadership and employee well-being is long established. In particular, health-oriented leadership is discussed as a leadership style specifically promoting employee well-being. However, the preconditions of health-oriented leadership remain largely unexplored. From the perspective of conservation of resources theory, leaders can only provide resources when receiving some themselves. We propose that organizational health climate (OHC) is an important organization-based resource for a health-oriented leadership style. More specifically, we hypothesize that the relationship between OHC and employee job satisfaction and emotional exhaustion is mediated by health-oriented leadership. We thereby differentiate two levels of analysis: a within-team level and a between-team level. We examined 74 teams with 423 employees of childcare centers at three time points, each six months apart. By means of multilevel structural equation modeling, we found OHC to be a significant antecedent of health-oriented leadership at the between-team level. The relationship between OHC and employee job satisfaction was mediated by health-oriented leadership at the between-team level, but not at the within-team level. The relationship between OHC and employee exhaustion showed another pattern of relationships at different levels of analysis, although it was not significantly mediated by health-oriented leadership. This indicates the value of differentiating between levels of analysis. We discuss the implications for theory and practice that can be drawn from our findings.